Toward an integrative socio-cognitive approach in autism spectrum disorder: NEAR method adaptation—study protocol - Bahri, Jihene; Abbes, Zeineb S.; Ben Yahia, Houda; Halayem, Soumeyya; Jelili, Selima; Hajri, Melek; Amado, Isabelle; Medalia, Alice; Bouden, Asma (Frontiers in Psychiatry, 2023)
Background: The cognitive impairments exhibited by people with ASD, threaten the development of social skills that are essential for establishing and maintaining harmonious social relationships. Cognitive remediation and social skills training are now considered as crucial therapeutic approaches in the management of these disorders. Several programs have already been validated and have shown improvements in social skills or cognitive performance. However, the effects of these training methods seem to be difficult to generalize to other everyday life. The aim of our study is to alleviate cognitive and social deficiencies by using a socio-cognitive framework to adapt the Neuropsychological Educational Approach to Remediation (NEAR) method for adolescents with ASD. Methods/Design: Adolescents meeting the DSM-5 criteria for ASD, older than 13 years, and following a regular school curriculum will be recruited from clinical population at the Child and Adolescent Psychiatry in Razi University Hospital-Manouba- Tunisia. Our study is an open and non-randomized controlled trial including 30 patients: NEAR group / control group. The NEAR method combines computerized cognitive exercises and bridging groups inspired from cognitive behavioral therapy. NEAR group will be divided into three groups of five patients each. The duration of the sessions will vary according to the capacities of the participants and the exchanges between them (about 60 minutes to 120 minutes). In our study, bridging groups will be amended by adding other tasks including planning role plays and scenarios of problematic social situations in autism, taking into account cultural particularities in order to promote social skills. Computerized exercises will be enriched by adding other tasks aiming to improve the recognition and expression of facial emotions by using digital videos and photographs expressing the six basic emotions. The duration of the program will be about 6 months. All selected patients will have an assessment of cognitive function: social cognition, neurocognition and pragmatic skills, social skills, self-esteem and global functioning at baseline, one week after the end of the NEAR program and six months later. . Conclusion: This adaptive program is a promising socio-cognitive intervention that create new perspectives for adolescents with autism spectrum disorder.